Effect of plastic waste types on pyrolysis liquid oil. (April 2017) - Miandad, R.; Barakat, M.A.; Aburiazaiza, Asad S.; Rehan, M.; Ismail, I.M.I.; Nizami, A.S.
Abstract: This paper aims to examine the effect of different plastic waste types such as polystyrene (PS), polyethylene (PE), polypropylene (PP) and polyethylene terephthalate (PET) on the yield and quality of produced liquid oil from the pyrolysis process. A small pilot scale pyrolysis reactor was commissioned for this purpose, and operated at optimum temperature and retention time of 450 °C and 75 min respectively. PS plastic waste showed maximum production of liquid oil (80.8%) along with least production of gases (13%) and char (6.2%) in comparison to other plastic types. Liquid oils from all plastic types contained mostly aromatic compounds with some alkanes and alkenes. Liquid oil from PS pyrolysis contained styrene (48.3%), ethylbenzene (21.2%) and toluene (25.6%). Pyrolysis liquid oils found to have ranges of dynamic viscosity (1.77–1.90 mPa s), kinematic viscosity (1.92–2.09 cSt), density (0.91–0.92 g/cm 3 ), pour point (−11(-60 °C)), freezing point (−15-(-65 °C)), flash point (28.1–30.2 °C) and high heating value (HHV) (41.4–41.8 MJ/kg) similar to conventional diesel, thus have potential as an alternative energy source for electricity generation. Upgrading of liquid oil using different post-treatment methods such as distillation, refining and blending with conventional diesel is required to make it suitable as a transport fuel due to presence of high aromatic compounds. The recovery of aromatic compounds especially styrene from pyrolysis oil can be a potential source of precursor chemical in industries for polymerization of styrene monomers. Graphical abstract: Highlights: PS plastic waste showed maximum production of liquid oil. PE plastic waste was converted into wax due to its long carbon chain structure. Liquid oils from all plastic types contained mostly aromatic compounds. Liquid oils had similar HHV to conventional diesel. Upgrading of liquid oil is required to make it suitable as a transport fuel.